In vitro characterization of gE negative bovine herpesvirus types 1.1 (BHV-1.1) and 1.2a (BHV-1.2a) - Spilki,Fernando R. (2004)
This study aimed the in vitro growth characterization of a previously constructed Brazilian bovine herpesvirus 1.2a with a deletion in the glycoprotein E gene (BHV-1.2a gE-). The plaque sizes, penetration and growth kinetics of the Brazilian BHV-1.2a gE- were studied and compared with the parental virus, as well as with a BHV-1.1 gE- recombinant derived from an European BHV-1.1 strain. No statistical differences were observed between the gE- recombinants and the respective parental viruses penetration assays were performed. When single step growth curves were studied, no statistical differences were observed between gE- and parental viruses. However, it was observed that both gE- viruses were excreted from cells in significantly higher titres at 11 hours post infection in comparison with parental viruses. No statistical differences were observed when plaque sizes of parental viruses or gE- viruses we analyzed separately in each cell type. However, both gE- recombinants displayed a significantly reduced plaque areas on three different cell cultures, in comparison with parental viruses, indicating that the lack of gE had the same effect on both BHV-1 subtypes, manifested by a restricted cell-to-cell spread in infected cells.